Blockchains as a means to promote privacy protecting, access availing, incentive increasing, ELSI lessening DNA databases - Gal Zarchi; Gal Zarchi; Maya Sherman; Maya Sherman; Omer Gady; Omer Gady; Tomer Herzig; Tomer Herzig; Ziv Idan; Ziv Idan; Dov Greenbaum; Dov Greenbaum; et al. (Frontiers Media S.A., 2023)
Not all blockchains are created equal, and many cannot accommodate all of the primary characteristics of big data: Variety, Velocity, Volume and Veracity. Currently, public blockchains are slow and clunky, it can be expensive to keep up with the velocity of genomic data production. Further, the transparent and universally accessible nature of public blockchain doesn't necessarily accommodate all of the variety of sequence data, including very private information. Bespoke private permissioned blockchains, however, can be created to optimally accommodate all of the big data features of genomic data. Further, private permissioned chains can be implemented to both protect the privacy and security of the genetic information therein, while also providing access to researchers. An NFT marketplace associated with that private chain can provide the discretized sale of anonymous and encrypted data sets while also incentivizing individuals to share their data through payments mediated by smart contracts. Private blockchains can provide a transparent chain of custody for each use of the customers' data, and validation that this data is not corrupted. However, even with all of these benefits there remain some concerns with the implementation of this new technology including the ethical, legal and social implications typically associated with DNA databases.